An exploratory investigation towards a visitor motivational profile at a provincial nature reserve in Gauteng - Davis Muzeza; Uwe P. Hermann; Pula S. Khunou (South African Journal of Business Management, 2018)
This study strives to address the needs of a Gauteng provincial nature reserve in order to develop a greater understanding of the visitors' profile to this reserve in terms of demographics and motivations for visitation. Understanding the motivations for different types of visitors is vital for reserve management to adequately satisfy the visitors' needs. An exploratory factor analysis was used to identify visitor segment profiles based on their motivations for visiting the reserve. The factor analysis revealed six motivation factors. These segments included relaxation and escape; nostalgia and history; personal benefits; wildlife and geographical features; convenience and part of lifestyle; and participating in an event. The study, furthermore, identified, for the first time at a South African provincial nature reserve, a new motivator factor: participating in an event. The results show that segmentation by motivation is a useful research tool for identifying what motivates visitors to travel. Understanding the differences within these segments will help management offer satisfying innovative activities and services to visitors. Recommendations for management include providing opportunities for nature enthusiasts by enhancing awareness creation of the fauna and flora present in the reserve as well as providing opportunities for relaxation and escape through the introduction of recreational facilities such as wellness programmes. Improved amenities are required such as refreshments, curios retail and overnight accommodation. The reserve appeals widely to mountain bikers; thus, marketing efforts should be directed towards this group.
Keywords: 650